Advances in simulation and process modelling Proceedings of the Second International Symposium on Simulation and Process Modelling (ISSPM 2020) - Li, Yupeng; Zhu, Quanmin; Qiao, Feng; Fan, Zhiping; Chen, Yinong (Advances in Intelligent Systems and Computing, 2021)
This book gathers the selected papers from the Second International Symposium on Simulation and Process Modelling (ISSPM 2020), which was held online on August 29-30, 2020, due to COVID-19 pandemic. The Symposium provides a forum in virtual presentation for scholars, researchers and practitioners who are interested in the modelling and simulation of business processes, production and industrial processes, service and administrative processes, and public sector processes to develop theory and practice of simulation and process modelling.